Stay awake ebook Stories. - Chaon, Dan (2012)
“Eerily beautiful . . . [Chaon] is the modern day John Cheever.”— Boston Sunday Globe   “Powerful and disturbing . . . The shocks in this collection are many.”— The Washington Pos t   These haunting, suspenseful stories by acclaimed author Dan Chaon feature scattered families, unfulfilled dreamers, anxious souls—lost, fragile, searching characters who wander between ordinary life and a psychological shadowland. They have experienced intense love or loss, grief or loneliness, displacement or disconnection—and exist in a twilight realm, in a place by the window late at night when the streets are empty and the world appears to be quiet. But it is not, and neither are you. And since you cannot sleep, you stay awake.   “Chaon is able to create fully realized characters in mere pages. . . . This collection is further proof that Chaon is one of the best fiction writers working right now.”— Omaha World-Herald   “There are not many fiction writers who can do what Dan Chaon can do. . . . [He is] a literary force.”— The Philadelphia Inquirer   “Intense and suspenseful . . . a highly recommended work, not to be missed.”— Library Journa l (starred review)   “Mesmerizing . . . gripping, masterful fiction.”— The Plain Dealer   “Superbly disquieting.”— The New York Times Book Review   Don’t miss the exclusive conversation between Dan Chaon and Emma Straub at the back of the book. Look for special features inside. Join the Circle for author chats and more.